The dance of the positives and negatives of life: Student wellbeing in the context of #FeesMustFall-related violence - Wilson Fadiji, A.; Luescher, T.; Morwe, K. (South African Journal of Higher Education, 2023)
Violence has become a regular occurrence in the context of the South African student movement. However, to date there are no studies that investigate student wellbeing in the context of student movement violence. How are violence and wellbeing experienced in the context of the student movement? What resources do students draw upon to protect or restore their wellbeing during and in the aftermath of violence? This article discusses students’ experiences of violence and wellbeing and particularly the resources that fostered their psychological wellbeing during and after experiences of violence related to the #FeesMustFall protests of 2015/16. The study used a photovoice methodology and worked with groups of former student activists from four universities in South Africa. Student psychological functioning in the midst of adverse circumstances is demonstrated in their ability to make meaning of their experiences by inventing knowledge spaces; creating spaces of inner harmony; having a sense of purpose; and protecting symbolic spaces of hope. It is also shown in their courage to challenge spaces of oppression. This study suggests that the co-production of social space for functioning occurs through an important psychological process of meaning-making that provides direction for student movement activities. Given our findings, it is recommended for student affairs and counselling services to m,./=-09864 facilitate the co-creation of spaces of knowledge and spaces of safety, spaces where students can experience being wanted and connected, and spaces where they can make sense of their experiences in the unfamiliar and potentially alienating higher education space.